Penganggaran caj kemasukan sesuai bagi taman-taman laut Malaysia : pendekatan penyenaraian kontigen - Jamal Othman; Norlida Hanim Mohd Salleh (Environmental Management Society, Malaysia, 2003)
This study utilizes the Contingent ranking technique to estimate the appropriate entrance fee level for Malaysian marine parks from the demand perspective. Appropriate entrance fee level optimizes recreationist satisfaction and visitation rate while generating sustained revenues for the maintenance of environmental quality. Questionnaires and survey for the first stage of the study were administered to some 282 visitor-respondents in Pulau Tioman in November 2000. The study shows that respondents on average derived positive utility (marginal values) from attributes such as snorkeling which reflects the importance of marine resource quality, jungle trekking which reflects the importance of inland greeneries, low development intensity which reflects the degree of “naturalness” of the marine parks, and the existence o9f traditional villages within the park. The current entrance fee level of RM5 per adult receptionist is found to be too low relative to the estimated net economic benefits of some RM44 for the case of Pulau Tioman. It is suggested that the fee be increased to some RM11 per entrance per adult person. This would allow some net benefits left to recreationist